Chinese calligraphy: Cultural appreciation for primary school students / Atiqah Nasuha Mohd Yazid Merman... [et al.] - Mohd Yazid Merman, Atiqah Nasuha; Ab Mutalib, Aina Farihah; Md Zaki, Siti Nur Syamira; Hashim Amir, Nur Muhammad Amin (UiTM Perak Press, 2022)
Education is more than learning and teaching, it is also a preparation that shapes experiences, and the best time to educate youths is as early as primary schools. Embarking in education requires nurture and practicality for students to experiences it first-hand. Young school students are curious, they would prefer visuals rather than textual, and that is what this paper is about. Teachers are not just there for teaching so that students will learn, but we need to create a moment that students can enjoy and remember out of a sheer will. The lesson plan is particularly discussing on Chinese calligraphy. Not only does this project promotes cultural appreciation for students but it also educates them on the gestural art in calligraphy. This paper is rather an anecdote for us teachers in the sense that we are sharing something that was not familiar culturally to us but, through art projects; appreciation for the culture of Chinese calligraphic writings is exposed for students to participate. In this paper, readers will find a brief history, the tools, the techniques, the benefits, and the results of conducting Chinese calligraphy as an art project in primary schools. Through art activities like this; students can learn art and culture while doing it with excitement.